2015
DOI: 10.1016/j.ijscr.2015.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Occult fracture of the femoral neck associated with extensive osteonecrosis of the femoral head: A case report

Abstract: HighlightsOsteonecrosis of the femoral head should be included in the differential diagnosis of insufficiency fracture of the femoral neck.Enhanced MRI may be useful in determining the existence of extensive osteonecrosis of the femoral head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…The sub-capital fractures associated to large osteonecrosis areas present a bad prognosis when they are managed with osteosynthesis, cases in which the performance of hip total arthroplasty is indicated. However, when they are associated to small necrosis lesions, the articular preservation measures, plus osteosynthesis with cannulate screws are useful, as in the case of our patient [1,2,17]. Ikemura et al showed such usefulness in the differentiation of the clinical characteristics of sub-capital fracture for insufficiency of the associated osteonecrosis, in which the risk factors play a fundamental role in such differentiation, because although most of the femoral neck fractures occurs with a latter osteonecrosis as complication, the not displaced fractures of the femoral neck, as a complication of the femoral head osteonecrosis, are very rare [17][18][19][20].…”
Section: Discussionmentioning
confidence: 88%
“…The sub-capital fractures associated to large osteonecrosis areas present a bad prognosis when they are managed with osteosynthesis, cases in which the performance of hip total arthroplasty is indicated. However, when they are associated to small necrosis lesions, the articular preservation measures, plus osteosynthesis with cannulate screws are useful, as in the case of our patient [1,2,17]. Ikemura et al showed such usefulness in the differentiation of the clinical characteristics of sub-capital fracture for insufficiency of the associated osteonecrosis, in which the risk factors play a fundamental role in such differentiation, because although most of the femoral neck fractures occurs with a latter osteonecrosis as complication, the not displaced fractures of the femoral neck, as a complication of the femoral head osteonecrosis, are very rare [17][18][19][20].…”
Section: Discussionmentioning
confidence: 88%
“…We treated our case with total hip arthroplasty. Fukui [10] reported a case of occult fracture of the femoral neck due to extensive ONFH in a 60-year-old man with hip pain. Yoon [11] reported an unusual case of ONFH that was misdiagnosed as a stress fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding fracture terminology : There exists a diversity in description of this fracture that develops in the setting of extensive ONFH (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). A stress fracture may be defined as a complete or incomplete Table I.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous subcapital fracture (SSF) of femoral neck complicating ONFH is an uncommon presentation and only a few cases have been reported so far (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). These reports largely present unilateral subcapital SSF of the femoral neck, with femoral head in various stages of osteonecrosis (3)(4)(5)(6)(7)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%